Production process and marketing system of cucumber: A socioeconomic study in Mymensingh district of Bangladesh (SAARC Journal of Agriculture, 2019)
The study was undertaken to evaluate the production process and marketing system of cucumber in Mymesingh district of Bangladesh. Primary data were collected from 50 stakeholders (30 farmers, 7 wholesaler, 7 retailers and 6 local traders) of Phulpur upazila and Mymensingh city. Purposive sampling technique was used to select the producers and convenience sampling was used for selecting the traders. The study revealed that production of cucumber was profitable in the study areas (with benefit cost ratio 1.59). Total marketing cost of cucumber was the highest for local traders (Tk. 2.73 per acre) and lowest for retailers (Tk.1.57per acre).In the study area, six market participants were identified which were producer, local trader, wholesaler, retailer, street seller and consumer. Gross and net marketing margin were the highest for retailers (4.25 Tk./kg and 2.65 Tk./kg, respectively). The study identified two cucumber marketing channels in Phulpur upazila and five in Mymensingh city. The seasonal price index of cucumber was the highest in the month of October (135.67) which indicated that price of cucumber in this month was 35.67 percent higher than average price and the lowest was in May (60.62). The result implied that price in this month was 39.38 per cent less than average price. The findings of this study about production, marketing function and seasonal price will help farmers and intermediaries involved with cucumber production and marketing to improve cucumber business.SAARC J. Agri., 17(1): 135-147 (2019)